Effectiveness of Educational Intervention Based on Theory of Planned Behavior for Increasing Breakfast Consumption among High School Students in Hamadan - Ali Mohammadimanesh; Fateme Rakhshani; Rozita Eivazi; Marym Farhadian (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Breakfast, the first meal of the day, provides children and adolescents with adequate nutrients. The purpose of this study was to investigate the effectiveness of an educational intervention to increase breakfast consumption among high school students in Hamadan based on the Theory of Planned Behavior (TPB). Materials and Methods: This quasi-experimental study was performed on 140 high school students (70 in the intervention group, 70 in the control group), selected by random sampling method. Data were collected using a self-report questionnaire containing items on demographic characteristics, and constructs of the TPB. In both groups, the questionnaires were filled out through interviews before and two months after the intervention. Participants in the intervention group received three sessions of training based on the constructs of the TPB. Data were analyzed in SPSS-19 using inferential statistics, such as the independent t-test, paired t-test and chi-square test. Results: The findings showed that the mean score of the constructs of the TPB (attitude toward the behavior, perceived behavior control and behavioral intention) in the intervention group did not significantly change after the intervention. Conclusion: Based on the results of this study, it is necessary that training programs for increasing breakfast consumption be conducted for longer periods and using other theories.